The determination of the spatial principal stresses changes based on the results of GPS measurements - Stanionis, Arminas (Geodesy and Cartography, 2012)
The changes of the Earth crust spatial principal stresses in the Ignalina nuclear power plant region based on the GPS measurements were determined by the method of tensor analysis. By applying the inverse Hooke’s law, new data of current Earth crust movement characteristics – spatial principal changes of stresses were calculated. The changes of the principal stresses vary from –0,082 to 0,112 MPa. It was determined, that the change of properties of principal stresses changes is regular, i.e. it is related to the distribution of tectonic breaks of the crystal substructure.Article in Lithuanian.Svarbiausiųjų erdvinių žemės plutos įtempių pokyčių nustatymas pagal GPS matavimų rezultatusSantrauka. Svarbiausiųjų erdvinių Žemės plutos įtempių pokyčiai pagal GPS matavimų Ignalinos atominės elektrinės rajone rezultatus nustatyti tenzorinės analizės būdu. Taikant atvirkštinį Huko dėsnį apskaičiuoti nauji dabartinių Žemės plutos judesių charakteristikos duomenys – svarbiausiųjų erdvinių įtempių pokyčiai. Jie siekia nuo –0,082 MPa iki 0,112 MPa. Nustatyta, kad svarbiausiųjų įtempių pokyčių savybių kaita yra dėsninga, t. y. susijusi su kristalinio pamato tektoninių lūžių išsidėstymu.Reikšminiai žodžiai: atvirkštinis Huko dėsnis, svarbiausiųjų erdvinių įtempių pokyčiai, GPS.First published online: 03 Aug 2012